2014
DOI: 10.1088/0004-637x/785/1/49
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anisotropies in Turbulent Magnetic Diffusion in Mean-Field Solar Dynamo Models

Abstract: We study how anisotropies of turbulent diffusion affect the evolution of large-scale magnetic fields and the dynamo process on the Sun. The effect of anisotropy is calculated in a mean-field magnetohydrodynamics framework assuming that triple correlations provide relaxation to the turbulent electromotive force (so-called the "minimal τ -approximation"). We examine two types of mean-field dynamo models: the well-known benchmark flux-transport model and a distributed-dynamo model with a subsurface rotational she… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…The flux transport dynamo with very complicated meridional flow patterns was investigated, and it was shown that if an equatorward flow in low latitudes at the bottom of the con-vective zone is present, the flux transport dynamo works even in the case of a meridional circulation with very complicated flow structures 47 . Similar works are seen for dynamos with double and multiple cells 48,49 , and dynamos in the global 3D simulations 50,51 .…”
Section: Introductionsupporting
confidence: 77%
“…The flux transport dynamo with very complicated meridional flow patterns was investigated, and it was shown that if an equatorward flow in low latitudes at the bottom of the con-vective zone is present, the flux transport dynamo works even in the case of a meridional circulation with very complicated flow structures 47 . Similar works are seen for dynamos with double and multiple cells 48,49 , and dynamos in the global 3D simulations 50,51 .…”
Section: Introductionsupporting
confidence: 77%
“…The eddy diffusivity is an order of 10 10 cm/s and less near the bottom of the convection zone. The diffusivity profile is the same as in our previous paper Pipin and Kosovichev [67].…”
Section: Resultsmentioning
confidence: 98%
“…where, E = u × b is the mean electromotive force with u and b standing for the turbulent fluctuating velocity and magnetic field respectively. Similar to our recent paper (see, [67,62]), we employ the mean electromotive force in form: where symmetric tensor α ij models the generation of magnetic field by the α-effect; antisymmetric tensorγ ij controls the mean drift of the large-scale magnetic fields in turbulent medium, including the magnetic buoyancy; the tensor η ijk governs the turbulent diffusion. The reader can find further details about the E in the above cited papers.…”
Section: Dynamo Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We employ the anisotropic diffusion tensor which is derived in P08 and in (Pipin & Kosovichev 2014):…”
Section: Angular Momentum Balancementioning
confidence: 99%